miR-466a Targeting of TGF-β2 Contributes to FoxP3+ Regulatory T Cell Differentiation in a Murine Model of Allogeneic Transplantation - Becker, William; Nagarkatti, Mitzi; Nagarkatti, Prakash S. (Frontiers in Immunology, 2018)
The promise of inducing immunological tolerance through Regulatory T cell (Treg) control of effector T cell function is crucial for developing future therapeutic strategies to treat allograft rejection as well as inflammatory autoimmune diseases. In the current study, we used murine allograft rejection as a model to identify microRNA (miRNA) regulation of Treg differentiation from naïve CD4 cells. We performed miRNA expression array in CD4+ T cells in the draining lymph node (dLN) of mice which received syngeneic or allogeneic grafts to determine the molecular mechanisms that hinder the expansion of Tregs. We identified an increase in miRNA cluster 297-669 (C2MC) after allogeneic transplantation, in CD4+ T cells, such that 10 of the 27 up-regulated miRNAs were all from this cluster, with one of its members, mmu-miR-466a-3p (miR-466a-3p), targeting TGF-β2, as identified through reporter luciferase assay. Transfection of miR-466a-3p in CD4+ T cells led to decreased inducible FoxP3+ Treg generation while inhibiting miR-466a-3p expression through Locked Nucleic Acid (LNA) resulted in increased Tregs, and a reduction in effector T cells. Furthermore, in vivo inhibition of miR-466a-3p in an allogeneic skin graft model attenuated T cell response against the graft through an increase in TGF-β2. TGF-β2 was as effective as TGF-β1 at both inducing Tregs, and, through adoptive transfer, mitigating host effector T cell response against the allograft. Together, the current study demonstrates for the first time a new role for microRNA-466a-3p and TGF-β2 in the regulation of Treg differentiation and thus offers novel avenues to control inflammatory disorders.